2020
DOI: 10.3389/fncel.2020.00275
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating and Sniffing Out the Neuromodulatory Roles of Dopamine in the Retina and Olfactory Bulb

Abstract: In the central nervous system, dopamine is well-known as the neuromodulator that is involved with regulating reward, addiction, motivation, and fine motor control. Yet, decades of findings are revealing another crucial function of dopamine: modulating sensory systems. Dopamine is endogenous to subsets of neurons in the retina and olfactory bulb (OB), where it sharpens sensory processing of visual and olfactory information. For example, dopamine modulation allows the neural circuity in the retina to transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 263 publications
(489 reference statements)
0
10
0
Order By: Relevance
“…Since dopaminergic neurons are believed to be the most important cells providing interglomerular connections (Aungst et al, 2003;Kosaka and Kosaka, 2008a;Kiyokage et al, 2010), sSA neurons were believed to be the only type of neuron expressing dopamine. However, a population of DA interneurons characterized by the absence of axons (Chand et al, 2015;Galliano et al, 2018) has been classified, based on the morphology of their dendritic arborization, as PG cells (Kosaka and Kosaka, 2009aKorshunov et al, 2020a;Kosaka et al, 2020).…”
Section: Juxtaglomerular Interneuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since dopaminergic neurons are believed to be the most important cells providing interglomerular connections (Aungst et al, 2003;Kosaka and Kosaka, 2008a;Kiyokage et al, 2010), sSA neurons were believed to be the only type of neuron expressing dopamine. However, a population of DA interneurons characterized by the absence of axons (Chand et al, 2015;Galliano et al, 2018) has been classified, based on the morphology of their dendritic arborization, as PG cells (Kosaka and Kosaka, 2009aKorshunov et al, 2020a;Kosaka et al, 2020).…”
Section: Juxtaglomerular Interneuronsmentioning
confidence: 99%
“…Immunohistochemical observations performed in the 80s' showed that mature DA neurons are strictly localized in the glomerular layer (Halasz et al, 1981). However, subsequent observations using a transgenic mice model, indicate that some neurons expressing eGFP under the TH promoter can be also observed in other layers including EPL, MCL and GCL (Baker et al, 2001;Pignatelli et al, 2009;Korshunov et al, 2020a;Kosaka et al, 2020). For these cells, the transcription of the TH gene occurs in absence of significant translational activity (Jeong et al, 2003).…”
Section: Electrophysiology Of Da Neurons During Adult Neurogenesismentioning
confidence: 99%
“…In earlier studies, we found elevated chemosensory rates in untreated lizards that interacted with AVT-treated males [Campos et al, 2020], but in this study, we found no evidence to suggest that central catecholamines in the FB are associated with chemosensory rates of behavior. Dopaminergic activity within the olfactory bulb influences olfactory sensitivity [Cave and Baker, 2009], with DA being essential to the regulation of odor detection and discrimination, and for processing visual stimuli [Korshunov et al, 2020]. Future studies are needed to assess whether DA concentrations in the olfactory bulbs are associated di-rectly with the performance of tongue flick behavior or the motivation to detect social chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons and neurotransmitters are not intrinsically inhibitory or excitatory, as can often be claimed (e.g., Eckstein et al, 2020 ). Inhibition and excitation as well as functions like mood (serotonin), reward (dopamine), and pain (substance P) are not intrinsic to a neuron or neurotransmitter but depend on the transmitter receptor activated, the cells the receptors are in, and the circuits/regions where the cells are located (dopamine is also involved in retinal processing ( Korshunov et al, 2020 ), 5-HT in motor control ( Jacobs and Fornal, 1993 ), and substance P in breathing ( Pilowsky, 2014 )). Consider the neurotransmitter GABA.…”
Section: Relational Aspects In Reductionist Schemesmentioning
confidence: 99%